Creative Management and Organization Effectiveness - Podlyashanik, V. V. (Psychological Prospects Journal, 2011)
Basic characteristics of creative management are presented in the article. Connection between creative management and effectiveness of organization functioning is out-lined by means of lighting conditions of creative management, professional qualities, skills and abilities of managers and methodological criteria for maturity-head leader.
Keywords: management organization creativity effective manager